Effect of molecular weights of chitosan coating on postharvest quality and physicochemical characteristics of mango fruit. (November 2016) - Jongsri, Pornchan; Wangsomboondee, Teerada; Rojsitthisak, Pranee; Seraypheap, Kanogwan
Abstract: 'Nam Dok Mai' mango is an important export fruit of Thailand. However, the quality of fruit is reduced after harvest. Therefore, it is necessary to develop a postharvest treatment to maintain the quality of 'Nam Dok Mai' mango after harvest. Chitosan solutions (high molecular weight (HM-CTS), medium molecular weight (MM-CTS), and low molecular weight (LM-CTS)) were applied as fruit coating for 'Nam Dok Mai' mango ( Mangifera indica L.) and stored at 25 °C for 16 days. The film forming properties of chitosan were influenced by molecular weight and significantly impacted postharvest quality of mango fruit during storage. HM-CTS could delay mango fruit ripening and thus maintaining the highest value of titratable acidity, fruit firmness, and also resulting in a reduction of weight loss, ethylene production, and respiration rate of mango fruit. Moreover, HM-CTS coated fruit exhibited no incidences of disease throughout storage. DPPH inhibition and ascorbic acid content were maintained in coated fruit during storage. H2 O2 content was inhibited by catalase and ascorbate peroxidase activities in HM-CTS coated fruit. These data indicated that the application of HM-CTS could be used to reduce deteriorative processes, maintain quality, and increase the shelf life of 'Nam Dok Mai' mango during postharvest storage. Highlights: Chitosan solutions were applied as fruit coating for 'Nam Dok Mai' mango fruit. Mango fruit coated with HM-CTS has the thickest chitosan film of all mango peel applied with chitosan solutions. The rate of respiration and ethylene production was lower in HM-CTS coated fruit. HM-CTS coating resulted in increased antioxidant contents. HM-CTS coated fruit exhibited no incidences of disease throughout storage.